Student Satisfaction with Online-Based Libraries Using Structural Equation Modelling - Achmad Danny Firmansyah; Atikha Sidhi Cahyana (UNIPA PRESS, 2023)
Online libraries are a development of conventional libraries that can make it easier for readers to get information anywhere without having to come to where the library is located. The existence of this can be the right solution during the current pandemic. Completeness and continuous updates can be an important factor for achieving success in attracting user interest. Structural equation modeling (SEM) is a useful statistical test measure that is useful for being able to complete a study simultaneously through indicators that affect service quality and user satisfaction. The results in this study found that service quality had no effect on user satisfaction with a CR value of 1.246 and a p value of 0.213 while online libraries had an effect on user satisfaction with a CR value of 5.282 and a p value of 0.000.